Dating human occupation and adaptation in the southern European last glacial refuge: The chronostratigraphy of Grotta del Romito (Italy). (15th March 2018) - Blockley, Simon; Pellegrini, Maura; Colonese, Andre C.; Lo Vetro, Domenico; Albert, Paul G.; Brauer, Achim; Di Giuseppe, Zelia; Evans, Adrian; Harding, Poppy; Lee-Thorp, Julia; Lincoln, Paul; Martini, Fabio; et al.
Abstract: Grotta del Romito has been the subject of numerous archaeological, chronological and palaeoenvironmental investigations for more than a decade. During the Upper Palaeolithic period the site contains evidence of human occupation through the Gravettian and Epigravettian periods, multiple human burials, changes in the pattern of human occupation, and faunal, isotopic and sedimentological evidence for local environmental change. In spite of this rich record, the chronological control is insufficient to resolve shifts in subsistence and mobility patterns at sufficiently high resolution to match the abrupt climate fluctuations at this time. To resolve this we present new radiocarbon and tephrostratigraphic dates in combination with existing radiocarbon dates, and develop a Bayesian age model framework for the site. This improved chronology reveals that local environmental conditions reflect abrupt and long-term changes in climate, and that these also directly influence changing patterns of human occupation of the site. In particular, we show that the environmental record for the site, based on small mammal habitat preferences, is chronologically in phase with the main changes in climate and environment seen in key regional archives from Italy and Greenland. We also calculate the timing of the transitions between different cultural phases and their spans. We also show that the intensification in occupation of the site is chronologically coincident with a rapid rise in Mesic Woody taxa seen in key regional pollen records and is associated with the Late Epigravettian occupation of the site. This change in the record of Grotta del Romito is also closely associated stratigraphically with a new tephra (the ROM-D30 tephra), which may act as a critical marker in environmental records of the region. Highlights: A revised Bayesian chronology for one of the key Late Upper Palaeolithic Records in Southern Europe. New radiometric ages on faunal material. Synchronous changes in local environment and regional environmental and climate change. The environmental context for human demographic changes in Southern Italy. A new tephra layer as a marker for environmental amelioration in Southern Italy during the Lateglacial.